2015
DOI: 10.2214/ajr.14.13426
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings of Fetal-Neonatal Ovarian Cysts Complicated With Ovarian Torsion and Autoamputation

Abstract: A complex heterogeneous ovarian cyst with a fluid-debris level indicating hemorrhage is a significant sonographic hallmark for the diagnosis of ovarian torsion. A calcified abdominal mass, with or without wandering, can be an autoamputated ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 19 publications
1
42
0
10
Order By: Relevance
“…Autoamputation, a rare but possible end result of ovarian torsion, has been described in previous reports as a free‐floating calcified or noncalcified mass in the abdominopelvic cavity . In our series, three patients had migration of the complex ovarian cyst on follow‐up imaging, and autoamputation was surgically confirmed in two of them.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Autoamputation, a rare but possible end result of ovarian torsion, has been described in previous reports as a free‐floating calcified or noncalcified mass in the abdominopelvic cavity . In our series, three patients had migration of the complex ovarian cyst on follow‐up imaging, and autoamputation was surgically confirmed in two of them.…”
Section: Discussionsupporting
confidence: 57%
“…In our series, three patients had migration of the complex ovarian cyst on follow‐up imaging, and autoamputation was surgically confirmed in two of them. According to a study by Ozcan et al, 10 of 11 patients who had calcifications in the cyst wall were found to have autoamputation, but sonography demonstrated wandering of the ovary in only two of these patients. Because the ovaries are more mobile in neonates and infants than in older patients, a change in location of the ovary does not always indicate the presence of autoamputation.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy is also used in gynecology to treat the torsion of ovaries still functioning [4]. In this case the diagnostic preoperative studies did not permit an adeguate diagnosis [3] but laparoscopy allows a correct diagnosis, to plan the surgical intervention and to avoid a wide laparotomy. Some authors has described laparoscopic removal of ovarian cysts.…”
Section: Discussionmentioning
confidence: 98%
“…Self amputated ovarian cyst is the result of an antenatal or neonatal torsion followed by calcification and necrosis. Laparoscopy is a minimally invasive diagnostic and operative technique whereby the surgeon can treat the affected side and observe the contralateral to decide if a prophilactic pexis if it is necessary [2,3]. Laparoscopy is also used in gynecology to treat the torsion of ovaries still functioning [4].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons that make surgery predominant are the torsion complication, the suspicion of a tumoral mass (though almost all of them are benign until 1 year of age), the fear of leaving necrotic tissue after auto-amputation, and the complication of intestinal obstruction (5,12,13). Those who recommend the expectant method argue that the postnatal operation performed with the prenatal diagnosis will not be effective, anesthesia taken during the first six months of life may have serious toxic effects, and malignancy in the first year is almost impossible (6).…”
Section: Discussionmentioning
confidence: 99%